Psychological Resilience and Career Readiness as Predictors of Entrepreneurial Intention Among Undergraduate Students in South Kalimantan - Muhammad Zainuddin; Agustino, Lalu; Satria Ramadhan Lihu, Mahesa Vicky (Lembaga Pengembangan Kinerja Dosen, 2025)
This study investigates the influence of psychological resilience and career readiness on entrepreneurial intention among undergraduate students in South Kalimantan, Indonesia. While previous research has predominantly focused on students from business faculties or those exposed to formal entrepreneurship programs, this study targets a more generalized student population to enhance the model’s applicability across disciplines. Using a quantitative research design, data were collected from 100 university students through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0.The results reveal that both psychological resilience (β = 0.539) and career readiness (β = 0.534) significantly and positively affect entrepreneurial intention, accounting for 72% of its variance (R² = 0.720). The findings highlight the importance of integrating psychological and career development factors into models of entrepreneurial behavior, especially in educational contexts with limited entrepreneurship exposure. The study contributes to theoretical advancements by validating a multidimensional framework and offers practical implications for educators, career counselors, and policymakers aiming to foster entrepreneurial potential among youth.These results suggest that entrepreneurship education should extend beyond technical skills and incorporate psychological capacity-building to better prepare students for uncertain career trajectories.